Evaluation of X-Inactivation Status and Cytogenetic Stability of Human Dermal Fibroblasts after Long-Term Culture. (24th November 2010) - Xue, Zhi-Gang; Shi, Zhan-Ping; Dong, Juan; Liao, Ting-Ting; Wang, Yan-Peng; Sun, Xue-Ping; Yan, Zheng-Jie; Qian, Xiao-Qiao; Cui, Yu-Gui; Chen, Juan; Liu, Jia-Yin; Fan, Guoping
Abstract : Human primary fibroblasts are a popular type of somatic cells for the production of induced pluripotent stem (iPS) cells. Here we characterized biological properties of primary fibroblasts in terms of cell-growth rate, cytogenetic stability, and the number of inactive X chromosomes during long-term passaging. We produced eight lines of female human dermal fibroblasts (HDFs) and found normal karyotype and expected pattern of X chromosome inactivation (XCI) at low passages (Passage P1-5). However, four out of the eight HDF lines at high passage numbers (≥ P 10 ) exhibited duplicated hallmarks of inactive X chromosome including two punctuate signals of histone H3 lysine 27 trimethylation (H3K27me3) and X inactive-specific transcript (XIST) RNA signals in approximately 8.5–18.5% of the cells. Our data suggest that the copy number of inactive X chromosomes in a subset of female HDF is increased by a two-fold. Consistently, DNA fluorescent in situ hybridization (FISH) identified 3-4 copies of X chromosomes in one nucleus in this subset of cells with two inactive Xs. We conclude that female HDF cultures exhibit a higher risk of genetic anomalies such as carrying an increased number of X chromosomes including both active and inactive X chromosomes at a high passage (≥ P 10 ).